The Potential Strategies of ZnIn2S4-Based Photocatalysts for the Enhanced Hydrogen Evolution Reaction - Tang, Meng; Yin, Weinan; Zhang, Feiran; Liu, Xia; Wang, Longlu (Frontiers in Chemistry, 2022)
Photocatalysis is a potential strategy to solve energy and environmental problems. The development of new sustainable photocatalysts is a current topic in the field of photocatalysis. ZnIn2S4 as a visible light responsive photocatalyst, has attracted extensive research interest in recent years. Due to its suitable band gap, strong chemical stability, durability, and easy synthesis, it is expected to become a new hot spot in the field of photocatalysis in the near future. This mini review presents a comprehensive summary of the modulation strategies to effectively improve the photocatalytic activity of ZnIn2S4 such as morphology and structural engineering, defects engineering, doping engineering, and heterojunction engineering. This paper aims to provide reference to the proof-of-concept design of highly active ZnIn2S4‐Based Photocatalysts for enhanced hydrogen evolution reaction.